A Proof-of-Concept Evaluation of the 1616 Story-Based Positive Youth Development Program - Jean Côté; Jennifer Coletti; Cailie S. McGuire; Karl Erickson; Kelsey Saizew; Alex Maw; Chris Primeau; Meredith Wolff; Brandy Ladd; Luc J. Martin (MDPI AG, 2023)
The 1616 Program is a newly developed and evidence-informed story-based positive youth development (PYD) program for young ice hockey players (10-12 years of age) in North America. The program uses elite ice hockey players as role models-through story-telling-to serve as inspirational figures to engage youth athletes and important social agents (i.e., parents, coaches) with evidence-informed PYD concepts. The objective of this study was to use a Proof-of-Concept evaluation to assess whether the 1616 Program 'worked' in enhancing PYD outcomes and to determine if the concepts were engaging and enjoyable for youth, their parents, and coaches. The 5 week Proof-of-Concept evaluation was conducted with 11 ice hockey teams (n = 160 youths, 93 parents, and 11 coaches), encompassing both qualitative (e.g., focus groups) and quantitative (e.g., retrospective pretest-posttest questionnaires) processes and outcome assessments. Results showed that the program was well received by participants and positively impacted the intended outcomes. Overall, the data presented in this Proof-of-Concept evaluation was deemed to support the development and implementation of the full-scale 1616 Program for a more comprehensive evaluation.